miR-151-3p Targets TWIST1 to Repress Migration of Human Breast Cancer Cells. - Ting-Chih Yeh; Tzu-Ting Huang; Tien-Shun Yeh; Yu-Ren Chen; Kai-Wen Hsu; Pen-Hui Yin; Hsin-Chen Lee; Ling-Ming Tseng (PLoS ONE, 2016)
TWIST1 is a highly conserved basic helix-loop-helix transcription factor that contributes to cancer metastasis by promoting an epithelial-mesenchymal transition and repressing E-cadherin gene expression in breast cancer. In this study, we explored the potential role of miR-151 in TWIST1 expression and cancer properties in human breast cancer cells. We found that the human TWIST1 3'UTR contains a potential binging site for miR-151-3p at the putative target sequence 5'-CAGUCUAG-3'. Using a TWIST1-3'UTR luciferase reporter assay, we demonstrated that the target sequence within the TWIST1 3'UTR is required for miR-151-3p regulation of TWIST1 expression. Moreover, we found that ectopic expression of miR-151-3p by infection with adenoviruses expressing miR-151 significantly decreased TWIST1 expression, migration and invasion, but did not affect cell growth and tumorsphere formation of human breast cancer cells. In addition, overexpression of the protein coding region without the 3'UTR of TWIST1 reversed the repression of cell migration by miR-151-3p. Furthermore, knockdown of miR-151-3p increased TWIST1 expression, reduced E-cadherin expression, and enhanced cell migration. In conclusion, these results suggest that miR-151-3p directly regulates TWIST1 expression by targeting the TWIST1 3'UTR and thus repressing the migration and invasion of human breast cancer cells by enhancing E-cadherin expression. Our findings add to accumulating evidence that microRNAs are involved in breast cancer progression by modulating TWIST1 expression.